Smooth Surface with U-grooved Structures for Light-detecting Area of Photodetectors Using Dual-doped Tetramethyl Ammonium Hydroxide - Kamonwan Suttijalern; Surasak Niemcharoen (Sensors and Materials, 2021)
Micro-electromechanical system (MEMS) fabrication has gained popularity as a means of etching silicon substrates. This paper discusses the surface texturization of a U-grooved structure by a very simple and cost-effective technique for use as a U-grooved metalsemiconductor-metal (UMSM) photodetector with aluminum/n-Si/aluminum materials. A series of etching experiments were carried out involving the addition of ammonium peroxodisulfate [(NH 4 ) 2 SO 4 ] at different concentrations to tetramethyl ammonium hydroxide (TMAH)/silicic acid etching solution, also called dual-doped TMAH. It was found that the addition of 11.5 g/l (NH 4 ) 2 SO 4 to TMAH/silicic acid enhances the smoothness of the surface and prevents the unwanted etching of exposed aluminum. We utilized dual-doped TMAH in the fabrication of a nanostructure in a U-grooved photodetector and found that the U-grooved photodetector has a ~59% higher photocurrent than that of a planar photodetector. The U-grooved photodetector demonstrates that increasing the light-detecting area results in high photocurrent performance for high-efficiency optical devices.
Keywords: Analytical Chemistry and Sensors